Effect of Pressure on Fabrty- Perot Interferometer Fringes Pattern. - Hussain, M.T.; Hatif, S.A.H.; Hadi, M.J. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A design and construction of Fabry -Perot Interometer  system  were achivcd to spcify  and  calculate wavelengths to the neart  nanometers for spectroscopic research investigation, this  accuracy  required  for as the refractive index is a function of pressure on the medium   when the space between  the two windows is keptn constant .He-Ne  laser (632.8)  nrn and  the green  laser (532)  nm  were  used  ascoherent sources.Lasers of  (632.8)  & (532)nm  respeCtively,  were  used  as  coherent sources. Results  showed accuracy  of (0.2)nm in determining  the wavelength when  (lOO) mm  Hg difference in  pressure  was  applied  . The   wavelength  and   the   refractive  index   were   calculated  when prcesure   was  varied  the  rough  Fabrt  -Perot  interferometer for  bth wavelengths.